Research Assessment in the Humanities 2016
DOI: 10.1007/978-3-319-29016-4_16
|View full text |Cite
|
Sign up to set email alerts
|

‘21 Grams’: Interdisciplinarity and the Assessment of Quality in the Humanities

Abstract: In their joint contribution, the president of the German Association for English Studies (Deutscher Anglistenverband), Klaus Stierstorfer, and the president of the German Association for American Studies (Deutsche Gesellschaft für Amerikastudien), Peter Schneck, describe the central motivations behind the decision to actively support the pilot study for the research rating of the German Council of Science and Humanities (Wissenschaftsrat) despite some fundamental skepticism among the associations's members. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The projects presented in this article show furthermore that if the assessment procedures adequately reflect the SSH research practices, scholars are ready to collaborate (for example, Giménez-Toledo et al, 2013;Ochsner et al, 2014) and to accept more easily research assessment, like in the Norwegian or German case (Aagaard et al, 2015;Sivertsen, 2016;Stierstorfer and Schneck, 2016). Full-coverage databases including all relevant document types are of value for scholarly work (Gogolin, 2016;Sandor and Vorndran, 2014a, b) and increase the visibility of humanities research production (Aagaard et al, 2015).…”
Section: Bottom-up Initiatives At the European Levelmentioning
confidence: 92%
See 1 more Smart Citation
“…The projects presented in this article show furthermore that if the assessment procedures adequately reflect the SSH research practices, scholars are ready to collaborate (for example, Giménez-Toledo et al, 2013;Ochsner et al, 2014) and to accept more easily research assessment, like in the Norwegian or German case (Aagaard et al, 2015;Sivertsen, 2016;Stierstorfer and Schneck, 2016). Full-coverage databases including all relevant document types are of value for scholarly work (Gogolin, 2016;Sandor and Vorndran, 2014a, b) and increase the visibility of humanities research production (Aagaard et al, 2015).…”
Section: Bottom-up Initiatives At the European Levelmentioning
confidence: 92%
“…In 2012, a pilot study in the humanities was eventually conducted. While still against the notion of quantifying research performance, the associations of English and American Studies decided to take part in the exercise (Stierstorfer and Schneck, 2016). The Wissenschaftsrat qualified the exercise as a success that showed that such a rating is possible in the humanities; the humanities scholars involved in the exercise acknowledged the effort by the Wissenschaftsrat to adapt the procedure to the humanities but also identified some negative aspects and consequences of the exercise, such as a division into different sub-disciplines instead of a focus on commonalities (Hornung et al, 2016).…”
Section: Ssh Research Practices and Criteria For Research Qualitymentioning
confidence: 99%